A Voronovskaya-type theorem - Ivan, Mircea; Raşa, Ioan (Rev. Anal. Numér. Théor. Approx., 2001)
We give an asymptotic estimation for some sequences of divided differences. We use this estimation to obtain a Voronovskaya-type formula involving linear positive operators.